The Mitigation of the Impossibility Concomitance of the Administrative and Judicial Tax Process (Global Journal of Management and Business Research, 2020)
It is an article of problematization of the normative device in the law of tax executions that unrestrictedly forbids a concomitance of administrative and judicial tax proceedings. To the job and division of judicial (judicial) in the division of trial and judicial judicial; (II) to make "State-judge-of-its-owncause" to the State of Weighting; (III) Object of the action as an affirmation of law.
Keywords: tax law; administrative tax process; power of tax